Robust gain switching control of constant bottomhole pressure drilling. (September 2017) - Nandan, Anirudh; Imtiaz, Syed; Butt, Stephen
Highlights: A robust controller design for managed pressure drilling (MPD) system under diverse operating conditions and parameter uncertainty is proposed. A gain switching linear controller based upon two parameters is proposed to handle the nonlinear MPD system. An observer was implemented for the constant bottomhole pressure (CBHP) drilling system for setpoint revision at the initiation of kick during drilling. The controller in combination with the observer can mitigate a bottomhole kick much faster compared to existing controllers. Abstract: Automation of managed pressure drilling is crucial in order to enhance safety. This process is highly nonlinear and the system varies considerably with changes in drilling conditions. In this work we have analyzed the effect of various operating conditions on plant parameters and designed a controller which will deliver consistent performance for different working conditions and will also be robustly stable. The control objectives of robustness and good performance are achieved by using multiple robust loop shaping controllers. Based on choke opening and mud flow rate, an appropriate controller is selected by utilizing a gain schedule. An observer for estimation of the reservoir pressure is also implemented so that an appropriate bottom hole pressure setpoint can be selected to maintain overbalanced conditions.